Efektivitas Media Game Edukasi Quizizz Dalam Meningkatkan Hasil Belajar Matematika Bilangan Bulat Pada Siswa SMP: Systematic Literature Review - Kartika Dewi; As Elly; Yufitriyanto (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
Mathematics learning on integer operations is often perceived by junior high school (SMP) students as abstract and challenging, contributing to low motivation and suboptimal learning outcomes. Quizizz, a gamified quiz-based platform, has been increasingly adopted in Indonesian mathematics classrooms as an interactive learning and assessment tool. This study aims to systematically review the effectiveness of Quizizz in improving mathematics learning outcomes among Indonesian secondary students, with particular attention to implications for integer instruction at the SMP level. Following the PRISMA 2020 protocol, twelve national studies published between 2020 and 2025 were identified, screened, and analyzed from academic databases including Google Scholar, Garuda, and DOAJ. The synthesis covers experimental, quasi-experimental, classroom action research, descriptive, research-and-development, and systematic-review designs. Findings show that Quizizz consistently enhances learning outcomes, motivation, conceptual understanding, and creative thinking skills across mathematics topics, supported by gamified features such as leaderboards, instant feedback, and a paper-mode alternative that align with self-determination theory, gamification principles, constructivism, and multimedia-learning theory. Effectiveness depends on question-design quality, pedagogical integration, and access to devices and internet. This review concludes that Quizizz is a promising instructional and formative-assessment tool for SMP mathematics, including integer material, and recommends further controlled experimental research focused specifically on integer topics with larger, more diverse samples.